PENEGAKAN HUKUM TINDAK PIDANA PERDAGANGAN ORANG PERSPEKTIF HUKUM PIDANA DAN HUKUM ISLAM DI WILAYAH HUKUM POLDA JAMBI - Rahman, Abdul; Ma'ani, Bahrul; Subhan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Human trafficking is a transnational crime that degrades human dignity, particularly among women and children. Although Law Number 21 of 2007 on the Eradication of Human Trafficking provides a firm legal instrument, trafficking cases within the jurisdiction of Polda Jambi continue to occur. This study aims to analyze the law enforcement of human trafficking within the jurisdiction of Polda Jambi, the obstacles and efforts involved, and the perspective of Islamic criminal law on this issue. An empirical juridical method was used, combining statutory, conceptual, and sociological approaches through library research and interviews with law enforcement officers. The results show that law enforcement has followed the stages of investigation through sentencing, yet remains suboptimal due to low public awareness in reporting, limited evidence, and increasingly digital methods used by perpetrators. From the perspective of Islamic law, human trafficking is prohibited as it violates the principles of protecting life (hifz al-nafs) and honor (hifz al-'ird), making perpetrators subject to ta'zir sanctions.